(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article analyzes today’s decisions and laws in the field of preschool education and foreign experience on the example of Russian preschool education and the use of effective methods in teaching English to children. features of the work to be carried out in the field of preschool education.